2022
DOI: 10.1155/2022/5048172
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Efficacy, Complications, and Inflammatory Reactions of Bridge Combined Internal Fixation System for Periarticular Fractures of the Shoulder

Abstract: Objective. The aim of the present research is to analyze the impact of the bridge combined internal fixation system (BCFS) on efficacy, complications, and inflammatory reactions of periarticular fractures of the shoulder. Methods. A retrospective analysis was performed on 100 patients with periarticular fractures of the shoulder admitted between January 2016 and January 2020. Patients were assigned to the observation group (OG) and control group (CG) according to different treatment schemes, with 50 cases in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Moreover, unstable intramedullary fixation greatly limits the treatment of comminuted fractures [ 12 , 14 , 15 ]. Many studies have reported the use of OBS for the extramedullary fixation of clavicle fractures, which potentially facilitates indirect fracture reduction without stripping the periosteum and promotes fracture healing via three-dimensional elastic fixation [ 26 , 27 ]. However, this approach has some limitations, including increased risks of hematoma, acromioclavicular pain, implant-related pain, and subcutaneous prominence of the nail rod [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unstable intramedullary fixation greatly limits the treatment of comminuted fractures [ 12 , 14 , 15 ]. Many studies have reported the use of OBS for the extramedullary fixation of clavicle fractures, which potentially facilitates indirect fracture reduction without stripping the periosteum and promotes fracture healing via three-dimensional elastic fixation [ 26 , 27 ]. However, this approach has some limitations, including increased risks of hematoma, acromioclavicular pain, implant-related pain, and subcutaneous prominence of the nail rod [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unstable intramedullary xation greatly limits the treatment of comminuted fractures [12,[14][15]. Many studies have reported on the extramedullary xation of clavicle fractures using the OBS, which potentially facilitates indirect fracture reduction without stripping the periosteum and promotes fracture healing via three-dimensional elastic xation [22][23]. However, this approach has certain issues, including hematoma, acromioclavicular pain, implant-related pain, and subcutaneous prominence of the nail rod, making it prone to complications [7].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%